2017
DOI: 10.1093/gbe/evx255
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral Genome Estimation Reveals the History of Ecological Diversification in Agrobacterium

Abstract: Horizontal gene transfer (HGT) is considered as a major source of innovation in bacteria, and as such is expected to drive adaptation to new ecological niches. However, among the many genes acquired through HGT along the diversification history of genomes, only a fraction may have actively contributed to sustained ecological adaptation. We used a phylogenetic approach accounting for the transfer of genes (or groups of genes) to estimate the history of genomes in Agrobacterium biovar 1, a diverse group of soil … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 67 publications
(86 reference statements)
8
48
1
Order By: Relevance
“…S2). Therefore, other analyses were conducted with the CNPSo 675 T strain to confirm that strains of genomospecies G1 might represent a new species, as indicated in previous studies [16, 17, 24, 47]. The clade Agrobacterium is characterized by the presence of a linear secondary chromosome (chromid) that requires a specific system to protect replicon ends (telomeres) against nuclease activity [1].…”
Section: Phylogenymentioning
confidence: 99%
“…S2). Therefore, other analyses were conducted with the CNPSo 675 T strain to confirm that strains of genomospecies G1 might represent a new species, as indicated in previous studies [16, 17, 24, 47]. The clade Agrobacterium is characterized by the presence of a linear secondary chromosome (chromid) that requires a specific system to protect replicon ends (telomeres) against nuclease activity [1].…”
Section: Phylogenymentioning
confidence: 99%
“…Members of the family Rhizobiaceae exhibit signs of replicon co-evolution (Slater et al 534 2009; Lassalle et al 2017;Wang et al 2018) and cross-replicon interactions (Ronson et 535 al. 1987;Heidelberg et al 2000;Barnett et al 2004;Bobik et al 2006;Galardini et al 536 2015; Pini et al 2015;Ramachandran et al 2017;diCenzo et al 2018), despite 537 remarkable strain-to-strain variation and the prevalence of large-scale rearrangements 538 in secondary replicons (Orozco-Mosqueda Mdel et al 2009;Mazur et al 2011;Lopez-the Ti plasmid of a different octopine-type strain of A. tumefaciens (Machida et al 1984) 562 and is part of a larger family of IS-elements found within a variety of bacteria (Han et al 563 2001; Gourbeyre et al 2010).…”
mentioning
confidence: 99%
“…To account for this, we relaxed our OG definition and used a heuristic mixing the formal orthology criterion and the unicopy criterion (Bigot et al 2013), where transfer events that do not increase the number of gene copies in a genome are ignored. We used a similar approach to differentiate additive and replacing gene transfer events in a previous study (Lassalle et al 2017) where it provided an evolutionary sound, yet conservative way of describing the structure of diversity within gene families. A last hurdle in the definition of OGs from reconciled gene trees is that trees from a sample are not guaranteed to have the same topology, nor the same events associated with them.…”
Section: ) Inference Of Orthology From Evolution Scenariosmentioning
confidence: 99%
“…By contrast, associations are unlikely to result from contingent causes if they were conserved over long periods of time during which purifying selection acted on the genomes. Moreover, genes that remain associated via events of co-transfer -which are unlikely under neutral conditions, due to random sampling of transferred genes and frequent genome rearrangements or gene losses -reflect the effect of strong selection for maintained gene linkage (Lassalle et al 2017). This indicates that long-term co-conservation patterns are relevant signatures of selection that can be applied to study the evolution of accessory genes.…”
Section: Introductionmentioning
confidence: 99%